THE EFFECT OF THE RECIPROCAL RELATIONSHIP BETWEEN THE EXCHANGE RATE AND MONETARY INFLATION IN IRAQ - Lect. Dr. Jabbar Saadoon Darag (Scholars Digest Publishing, 2024)
The research aims to study the reciprocal relationship between the exchange rate and inflation for the period (2004-2022), and deals with the concept, role and factors affecting the exchange rate, as well as the concept of inflation and what are the factors affecting inflation. The data required for the study were obtained through the Central Bank of Iraq. In this study, the study of autocorrelation, and through the results, it was shown that there is a relationship between the two variables in the short term, and the existence of a long-term relationship between them, and through a program and a cointegration test, through the Engel-Graniger test model, and testing the two variables in the two cases and each variable separately, once. One is independent and another is dependent on both variables.
Keywords: exchange rate; Inflation rate; ARDL model.